The impact of network size on bank branch performance - Beverly J. Hirtle (Federal Reserve Bank of New York, 2005)
Despite recent innovations that might have reduced banks' reliance on brick-and-mortar branches for distributing retail financial services, the number of U.S. bank branches has continued to increase steadily over time. Further, an increasing percentage of these branches are held by banks with large branch networks. This paper assesses the implications of these developments by examining a series of simple branch performance measures and asking how these measures vary, on average, across institutions with different branch network sizes. The key findings are that banks with 100 to 500 branches (mid-sized networks) had lower bank-average deposits per branch and roughly equal volumes of small business loans per branch, but no reduction in net deposit costs, relative to banks with larger branch networks. When compared to banks with 100 or fewer branches, mid-sized branch networks had lower bank-average deposits and small business loan volume per branch, but had lower net deposit costs. The analysis shows no systematic relationship between branch network size and overall institutional profitability. The results imply that mid-sized branch networks may be at a competitive disadvantage, especially relative to the very largest branch networks.
Keywords: G21; G28; L11; L89; 330; banking; branch; deposits; Bank; Filiale; Einlagengeschäft; Unternehmenserfolg; USA